Surgeons' participation in the development of collaboration and management competencies in undergraduate medical education - Rothdiener, Miriam; Griewatz, Jan; Meder, Adrian; Dall'Acqua, Alessandro; Obertacke, Udo; Kirschniak, Andreas; Borucki, Katrin; König, Sarah; Rüsseler, Miriam; Steffens, Sandra; Steinweg, Bernhard Albert; Lammerding-Köppel, Maria (PLOS ONE, 2020)
The teaching of professional roles in medical education is an interdisciplinary concern. However, surgeons require specific standards of professionalism for certain context-based situations. In addition to communication, studies require collaboration, leadership, error-/conflict-management, patient-safety and decision-making as essential competencies for surgeons. Standards for corresponding competencies are defined in special chapters of the German National Competency-based Learning Objectives for Undergraduate Medical Education (NKLM; chapter 8, 10). The current study asks whether these chapters are adequately taught in surgical curricula. Eight German faculties contributed to analysing mapping data considering surgical courses of undergraduate programs. All faculties used the MERlin mapping platform and agreed on procedures for data collection and processing. Sub-competency and objective coverage, as well as the achievement of the competency level were mapped. Overall counts of explicit citations were used for analysis. Collaboration within the medical team is a strongly represented topic. In contrast, interprofessional cooperation, particularly in healthcare sector issues is less represented. Patient safety and dealing with errors and complications is most emphasized for the Manager/Leader, while time management, career planning and leadership are not addressed. Overall, the involvement of surgery in teaching the competencies of the Collaborator and Manager/Leader is currently low. However, there are indications of a curricular development towards explicit teaching of these roles in surgery. Moreover, implicitly taught roles are numerous, which indicates a beginning awareness of professional roles.
Gesehen am 11.05.2021